Weaving Central Java’s folktales into a digital fairytale storybook: A creative approach to teaching reading - Maria Dimitrij Angie Pavita; Aziza Restu Febrianto; Allvian Ika Fiki Susanto (Universitas Muhammadiyah Malang, 2025)
This research aims to find out the design a digital fairy tale story book based on Central Java Folktales. In this research, the method was developmental research that used Research and Development (R&D) model proposed by Borg and Gall. R&D instructional design was implemented as the phase in developing the materials. The R&D model consists of ten systematic stages that guide the development process in a structured manner. However, for this study, the researcher selects five of the ten stages based on their relevance to the research objectives. To collect the data, the researcher used questionnaire to get a validation by the expert. Moreover, teachers believe the storybook fits well with what kids need to learn reading. It's not meant to replace regular reading materials, but it can be a great way to make learning more fun and engaging. The storybook gives teachers a tool they can easily use to make reading more exciting for their students and help them become better readers. It is a practical and ready-to-use resource that can make a real difference in early reading instruction. Because it's digital, it's also easy to share and access, making it even more useful for teachers and students.